Voluntary Forelimbs Exercise Reduces Immobilization-Induced Mechanical Hyperalgesia in the Rat Hind Paw. (7th August 2021) - Ishikawa, Kumiko; Oga, Satoshi; Goto, Kyo; Sakamoto, Junya; Sasaki, Ryo; Honda, Yuichiro; Kataoka, Hideki; Okita, Minoru
Abstract : Voluntary exercise is sufficient to protect against neuropathic pain. However, it is unclear whether voluntary exercise reduces immobilization-induced hyperalgesia. We examined the effect of voluntary forelimb exercise on immobilized-induced hyperalgesia in hind paws of rats. Wistar rats were randomly divided into the (1) both hind limbs immobilized group (IM group), (2) immobilization and exercise with nonimmobilized fore limbs group (EX group), and (3) control group. In the IM and EX groups, the bilateral ankle joints of each rat were immobilized in full plantar flexion with a plaster cast for eight weeks. In the EX group, voluntary exercise using nonimmobilized forelimbs in the running wheel was administered during the immobilization period, while hind limbs were kept immobilized (60 min/day, 5 days/week). Mechanical hyperalgesia in the hind paw was measured using a digital von Frey device every week. To investigate the abnormality of primary sensory neurons and central sensitization, the number of calcitonin gene-related peptide-positive cells in the dorsal root ganglion and the expression level of calcitonin gene-related peptide in the spinal dorsal horn were analyzed by immunohistochemical staining. Immobilization-induced mechanical hyperalgesia was inhibited in the EX group compared to the IM group at three weeks after immobilization. In the EX group, the number of calcitonin gene-related peptide-positive cells in the dorsal root ganglion and the expression level of calcitonin gene-related peptide were significantly decreased compared to those in the IM group. Our results therefore suggest that voluntary forelimb exercise during hind limb immobilization partially reduces immobilization-induced hyperalgesia by suppressing that the plastic changes of the primary sensory nerves that excessively transmit pain and increased responsiveness of nociceptive neurons in the spinal dorsal horn.